Pemanfaatan Artificial Intellegence Dalam Pembuatan Karya Intelektual - Siswanto Siswanto; Desi Mahdalena; Nofi Qurniat; Ahmad Arib Al Farisy; Rizki Amelia (Jurnal Dehasen Untuk Negeri, 2024)
This community service activity aims to improve students' understanding of artificial intelligence utilization in creating intellectual works at Madrasah Aliyah Pancasila Bengkulu. The main issue is the low utilization of digital technology, especially artificial intelligence, in supporting learning processes. The solution offered is educational socialization using lectures, discussions, and evaluation methods. The activity was conducted through observation, preparation, implementation, and evaluation stages. The results indicate an increase in students' knowledge regarding the use of artificial intelligence and its positive and negative impacts. Students also showed high enthusiasm during the activity. Therefore, this program contributes to improving digital literacy and preparing students for rapid technological advancements.